IMPACT OF MACRONUTRIENTS ON THE PRODUCTION OF CLEAN AND HEALTHY MANGO NURSERY PLANTS IN POLYBAGS UNDER NURSERY TUNNEL - IQBAL, A; MUSTAFA, G; IMRAN, M; HAMEED, A; HUSSAIN, R; HUSSAIN, N; KIRAN, S; IQBAL, J; AIN, NU; SHAH, SAH (Biological and Clinical Sciences Research Journal, 2022)
Mango nursery production under polybags is highly depend on application of various fertilizers for developing healthy and vigorous nursery plants. Mango nursery was grown in polybags placed undera nursery tunnel. The fertilizer (N:P:K 20:20:20) were applied as control or no application, 5g, 10g, 15g and 20g into the polybags after 30 days of seedling transplanting into poly pots followed by irrigation of 500ml water into the pots. The data was recorded after 30, 60 and 90 days intervals in terms of plant height, root length, number of leaves per plant, and number of vegetative flushes per plant after applying nutrition to the plants. The results revealed that the maximum plant height of 67.21cm was observed when pots were fertilized @ 10g per pot followed by irrigation of 500ml water. In comparison,the root length was 22cm, number of leaves per plant was 31.33, and the number of vegetative flushes 8 per plantwasobserved when mango nursery pots were fertilized with 10g per pot.